Smart Penataran: Transformasi Digital Desa Wisata Candi Menuju Masyarakat Sejahtera dan Berdaya Saing : Penelitian - Habib Bawafi; Puji Asmaul Chusna; Lailatul Mubarakah; Mada Purwa H.; Kunti Alfi H.; Afif Mustafa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the implementation and impact of the Smart Penataran program in the digital transformation of Penataran Temple Tourism Village towards a prosperous and competitive society. Using a mixed-methods approach with 156 respondents over 8 months (March-October 2025), the study measured improvements in digital literacy, economic impact, and social empowerment. The results showed a significant increase in digital literacy from 1.8 to 3.9 (116.7%), with an economic impact in the form of an average increase in MSME income of 110.3%. The program, implemented in three phases—digital infrastructure development, capacity building, and mentoring—successfully transformed 45 MSMEs into digital businesses and increased tourist visits by 175.6%. The Cost-Benefit analysis showed high feasibility with a BCR of 3.92 and a payback period of 2.8 months. The social transformation was marked by an increase in women's participation from 28% to 56% and the emergence of 7 digital youth groups. The Village-Owned Enterprise-based platform model generated sustainable revenue of IDR 34 million/month. The study concluded that digital transformation with a holistic approach—integrating technological infrastructure, capacity building, and participatory governance—can be a catalyst for inclusive economic development and sustainable tourism development, offering a blueprint for replication in other tourism villages.